A SIMULATION STUDY OF SDN DEFENSE AGAINST BOTNET ATTACK BASED ON NETWORK TRAFFIC DETECTION - hadianto, rahmadani (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2018)
This paper discusses the Software Defined Networking (SDN) security experiment on Zeus Botnet attacks based on traffic behavior in the network. The development of SDN technology is increasingly in demand today, both on the researcher and industry side. This is inseparable from the SDN feature that gives the developer the flexibility to program the system inside. But on the other hand, the development of network technology cannot be separated from the threat of attack, especially Botnet attacks. Botnets are able to take control of the SDN network by attacking the control plane. This is possible when the botmaster enters a third party into the network and infects the associated device in the SDN network as a bot. This problem is categorized as Integrity in CIA triad (Confidentiality, Integrity, and Availability) used in the evaluation of security performance. Integrity in the CIA triad is a state of information that is always accurate and consistent until a recognized user makes a change. At the end of this paper will be explained about future research based on experimental test results.